The Development of Learning Media for Circulatory System Submaterial Using Microsoft Sway Based on Inquiry to Improve Scientific Literacy - Permatasari, Nita Avilia; Puspitawati, Rinie Pratiwi (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2025)
Scientific literacy is one of the most important skills that learners must have to apply science appropriately. The inquiry approach is a learning strategy that can improve scientific literacy. This research aims to produce learning media for circulatory system submaterial using Microsoft Sway based on inquiry to improve scientific literacy based on validity, practicality, and effectiveness. This learning media was developed using the ASSURE model, namely analyze learner, state performance objectives, select methods, media, and materials, utilize media and materials, requires learner participation, evaluate and revise. This learning media was tested on 20 students of class XI at Labschool Unesa 1 Surabaya High School. The parameters in this research include validity based on the validation results of the validators, practicality based on the results of students' responses to the use of learning media, and effectiveness based on the results of N-Gain scores, sensitivity index and achievement of scientific literacy of students after using learning media. The research data analysis method was quantitative descriptive. The results of the analysis showed that the learning media that had been developed obtained a validity score of 98.02% (very valid), a practicality score of 97.81% (very practical), and an effectiveness score obtained from the N-Gain of 0.8 (high) sensitivity index of 0.39 (sensitive), as well as the achievement of scientific literacy indicators, namely describing phenomena scientifically 80%, formulating questions that can be investigated scientifically 85%, conducting scientific investigations 90%, evaluating the results of scientific investigations 85%, analysing data tables scientifically 90%, and producing conclusions based on data and scientific evidence 90%. Thus, this learning media is suitable for use in learning to improve students' scientific literacy.